Evaluation of The Potential of Amaranth Flour for Lactic Acid Fermentation - Z. Matejčeková; D. Liptáková; Ľ. Valík (Journal of Pharmacy and Nutrition Sciences, 2016)
Although cereals and pseudocereals are deficient in some basic components, fermentation process is the most economical and simple way, how to improve nutritional value, functional qualities and sensory properties of the final products. In our study, we focused on the evaluation of amaranth flour for preparation of new probiotic functional foods suitable for celiac patients. That is why the growth dynamics of several Lactobacillus sp. in amaranth mashes were evaluated. All the monitored strains showed sufficient growth in mashes (growth rates of lactobacilli ranged from 0.73 to 1.52 h-1). Based on the rates, only Lb. rhamnosus VT1 was able to grow with the values higher than 1.38 h-1 in both milk and water based mashes. In the second part of our study, we described behaviour of Lb. rhamnosus GG in amaranth water- or milk- based mashes after 8 h of co-cultivation with Fresco DVS 1010 culture (37 ± 1 °C, 5 % CO2). Final counts after the fermentation reached values 108 CFU.ml-1 and no decrease was recorded during 2-week storage period at 6 ± 1 °C. Thus we may conclude that densities of lactobacilli were able to maintain above the limit of >106 CFU.ml-1 essential from the legislation point of view.